LC-MS guided isolation and dereplication of Lycopodium alkaloids from Lycopodium cernuum var. sikkimense of different geographical origins. (April 2019) - Tang, Yu; Li, Na; Zou, Yike; Ai, Yanran; Ma, Guang-Lei; Osman, Ezzat E.A.; Xiong, Juan; Li, Junmin; Jin, Ze-Xin; Hu, Jin-Feng
Abstract: Lycopodium alkaloids (LAs) are the characteristic metabolites of club mosses. Chemical differences often exist in different specimens of a single plant species collected from different geographic origins. In this study, a preliminary LC-MS detection and dereplication analyses of alkaloidal constituents of Lycopodium cernuum var. sikkimense (Müll. Hal.) C.B. Clarke (LCVS2) collected from Fujian province led to the isolation and characterization of three undescribed LAs, lycocernuskines A–C, and six known cernuane-type LAs. The known compounds were previously isolated from the same plant species (LCVS1) collected from Chongqing, and so their dereplication in LCVS2 was accomplished based on their retention times ( t R ) and the quasi-molecular ion peaks in the LC-MS fingerprint. Chemical structures were identified by spectroscopic methods, single-crystal X-ray diffraction analysis, and electronic circular dichroism calculations. Lycocernuskines A and B are the first two examples of C-12 hydroxylated phlegmarane-type LAs bearing a nitrone residue at the quinoline ring. The isolates were evaluated for their anti-AChE and neuroprotective effects. Graphical abstract: LC-MS method was applied to the isolation and dereplication of Lycopodium alkaloids (LAs) from samples of the same Lycopodiaceae species ( Lycopodium cernuum var. sikkimense ) collected in two different locations. Three undescribed LAs were thereafter obtained and characterized . Lycocernuskines A (1 ) and B represent the first two examples of C-12 hydroxylated phlegmarane-type LAs bearing a nitrone residue at the quinoline ring.Image 1 Highlights: LC-MS guided isolation and dereplication of Lycopodium alkaloids (LAs) was applied. Three undescribed LAs were obtained from Lycopodium cernuum var . sikkimense. Lycocernuskines A and B are unusual nitrone-containing 12-hydroxy-phlegmarane LAs. The absolute configurations of lycocernuskines A and B were determined.